Scattering matrix analysis of a gyrator circulator - Prasad L.; Jha R.K. (My University, 2025)
The principle of operation of the gyrator circulator has been explained with the help of it scattering matrix. It is shown that power flow can take pleco from port A to H, 13 to C and so on, i.e. in one particular sequence. It has also been proved that there is no cross coupling of power. © 1973 Taylor & Francis Group, LLC.